1990
DOI: 10.1007/bf00844834
|View full text |Cite
|
Sign up to set email alerts
|

Assessing skills for refusing cigarettes and smokeless tobacco

Abstract: Hops and colleagues developed an audiotaped refusals skills test in which students respond to cigarette offers and their responses are scored for content. The present study employed a modified analogue skills test. Modifications included adding a separate subscale for smokeless tobacco, emphasizing repeated offers and group pressure, and rating the quality of responses (good, fair, poor). The test was evaluated in four seventh-grade classrooms (N = 78). Half had participated in a refusals skills training progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…12,13,19,24 Although these studies report high interrater reliability, they provide no explanations of what makes a student more or less effective in the eyes of the raters. In an interesting exception, one study 26 examined associations between adult raters' assessments of refusal skill effectiveness and specific nonverbal behaviors in a role-play.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…12,13,19,24 Although these studies report high interrater reliability, they provide no explanations of what makes a student more or less effective in the eyes of the raters. In an interesting exception, one study 26 examined associations between adult raters' assessments of refusal skill effectiveness and specific nonverbal behaviors in a role-play.…”
mentioning
confidence: 97%
“…[12][13][14][15] These strategies involve a combination of verbal and nonverbal assertive skills that can be applied to any request to engage in a problematic behavior. Although previous studies have examined the types of refusal strategies normally generated by adolescents, [16][17][18][19][20][21] the degree to which these strategies are similar across problem behaviors has gone relatively unexplored. The current study examines young adolescents' use of re-fusal skill strategies in role-play situations with 2 different contexts: offers to smoke and to shoplift.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have disagreed about what constitutes a specific effective response, however. Using a direct and simple "no" and giving an excuse, for example, have been considered effective in some studies [16,17] and less effective in others because they have been found to invite further pressure and negotiation [18,19]. For the purposes of this study, socially appropriate responses include a simple and direct "no," direct simple statements of the adolescent's position, and offers of prosocial alternatives.…”
mentioning
confidence: 97%
“…Prior studies showed that simple refusal and explaining were effective resistance strategies for adolescents (Sallis, Elder, & Wildey 1990; Turner, Burciaga, Sussman, & Klein-Selski 1993). In this study, latent class analysis indicates that LEAVE and AVOID strategies appear to drive the observed effects in defining skill profiles more so than REFUSE and EXPLAIN in this sample.…”
Section: Discussionmentioning
confidence: 99%